Irrational Beliefs and Personality Traits as Psychological Mechanisms Underlying the Adolescents' Extremist Mind-Set - Trip, Simona; Marian, Mihai Ion; Halmajan, Angelica; Drugas, Marius Ioan; Bora, Carmen Hortensia; Roseanu, Gabriel (Frontiers in Psychology, 2019)
The tripartite model of militant extremist mind-set proposed by Stankov et al. (2010b) includes three components: War (justification of violent acts); God (extremist acts are moral because they are done in the name of God/Allah); and West (violence against Western countries is justified because they are perceived as evil). There is a lack of conceptual framework regarding psychological mechanism that underlie radicalization and extremism, and there is little evidence regarding risk factors for radicalization in the scientific literature. In the present study, it is hypothesized that irrational beliefs and a constellation of personality factors are two possible psychological mechanisms that put adolescents in a vulnerable position and could influence them to develop an extremist mind-set. The sample consists in 295 Romanian adolescents, ages 15-18 years, and the mean age being 16.41. The present study was conducted in several schools from Bihor County located in the north-western part of Romania. Adolescents took part on a voluntary basis in the study after the written, informed consent was obtained from their parents. A confirmatory factor analysis (CFA) on the structure of Militant Extremist Mind-Set Scale confirmed the three-factor model of the extremist mind-set. Two confirmatory factor analyses were also conducted for the other two administered scales: CASI and Mini-IPIP. The results support the previous models for both subscales, including items loading on factors. SEM analysis was performed with AMOS 23 statistical package on a final sample size of 242 participants and there were no missing data. Fifth structural models were specified. The fifth model had adequate fit based on all three indices including the RMSEA (0.054), CFI (0.958), and SRMS (0.047). Global evaluation of self seems to be the only irrational belief that was somewhat related with the extremis mind-set, being part of it. Neuroticism was not identified as being a variable that could have a direct influence on mind-set extremism, or an indirect influence through personality. Religious adherence is a good predictor of extremist ideology. A global personality factor consisting in low Intellect/Imagination, low Extraversion and high Agreeableness seems to be a vulnerability factor that influences people to believe in extremist ideology.